Evaluation of a training experience for university professors in the development of digital educational resources - Cardona Román, Diana Marcela; Candolfi Arballo, Norma; Sánchez Torres, Jenny Marcela (Rastros Rostros, 2016)
Introduction: The evaluation of the results of a training in educational resources for teachers from the Engineering and Technology Center at the Universidad Autónoma de Baja California was proposed as a strategy of inter-institutional collaboration between Mexico and Colombia. Methodology: The type of research used was descriptive with a mixed approach. Data were collected using a survey instrument of 13 questions and a purposive sample of 10 teachers. Results: Eight variables (gender, age, teaching method, expectations, relevance, motivation, student learning, and tools) were defined, the internal consistency of the instrument (Pearson correlation coefficient of 0.879, Cronbach’s alpha of 0.947) was evaluated, and it was found that a training designed to meet real needs has a positive impact on teachers. Conclusions: The planning of and participation in trainings increases the motivation and interest of teachers. Trainings also foster a favorable environment for the incorporation and use of teaching resources in virtual classrooms as a teaching strategy.
Keywords: training; technology assessment; teacher training; educational resources; university